Railroad of death - Coast, John 1916-1989 (Myrmidon, 2014)
John Coast was a young British Army officer who was taken prisoner at the Fall of Singapore in February, 1942. He took notes and concealed them from the Japanese for nearly three years, but lost them when he was forced to bury them to avoid repeated searches. Coast had to write the book all over again while on the voyage home. His book is moving, dramatic, and chilling in the detail it gives of the cruelty inflicted by Japanese and Korean soldiers on the prisoners and Asian workers who died in even greater numbers working on the railway. Yet it is at the same time lyrical in its descriptions of the natural world surrounding the camps and the food and kindness shown by some Thais to the prisoners. Coast brings to life the camps and towns of the Burma Railway and the culture of Bali and Indonesia that allowed him to find some comfort and meaning amid the horror. This new edition has an introduction and appendices which include transcriptions of his BBC interviews with his Japanese captors and Takashi Nagase. Other appendices include never before published documents which help reveal details about secret radios and attempted escapes masterminded by the talented group of officers around Coast. It also includes an index and list of newly identified individuals mentioned in the book.